"Every day is filled with unexpected violations": examining the continuum of disability hate crime for disabled women - Mason-Bish, Hannah (Disability hate crime, 2025)
Disabled people face ableist assumptions and challenges which shape their everyday encounters when in public spaces. The development of hate crime policy has slowly begun to pay attention to this, yet the gendered nature of disability hate crime remains underexplored. Disabled women experience hostility, abuse, sexual harassment, and unwanted comments. Their bodies are hyper-visible in public spaces and subject to public gaze and diagnostic questioning. These assessments come from an ableist and sexist entitlement to intrude on the movements of disabled women. Drawing on data from a research project, the chapter explores the nature and impacts of non-consensual touching experienced by disabled women in their daily lives. I explore the emotional labour required of them and the impact it has on their sense of self. Finally, I examine the deeper, embodied impacts of these intrusive behaviours and how they remove agency from those experiencing them. This will be framed by a broader question about why disabled women have often been left out of hate crime policy discussions.